A formação continuada de professores na educação infantil: diálogos entre a produção acadêmico-científica e a pesquisa-formação - Bitencourt, Juverci Fonseca (2017)
It produces a goal-analysis about teachers’ continuing education of basic education, especially in the early childhood education, analyzing the academic production in the period from 1996 to 2014. It promotes interventions in the early childhood school by the research-training, enhancing the experience narratives from teachers’ training. It comprises the place of continuing education at the early childhood school in its relation with the assumptions discussed in the academic production within this field of study. It is conducted by the bibliographic research, using bibliometrics indicators, the app Iramuteq and the production of analytical categories for text processing. It adds to this methodological corpus the research-training through participating observation, the semi-structured interviews, the reflective workshops and the journal. It enhances, for the theoretical support, the authors Antônio Nóvoa, Walter Benjamin and Michel de Certeau, backing up debates on experience, professionality, institutionality of scientific journals and epistemology of practice. The results expose, in the scene of academic production, the little attention destined by the analyzed scientific journals to early childhood education. The debate on continuing education in the basic education establishes teacher’s practice as first in the proposition and the direction of these trainings. It presents the concentration of academic production in six categories and 70 thematic, with emphasis on intervention analyzes, literary analyzes and analyzes of proposals, programs and continuing education projects. It possibil It enables, through research-training, the production of the pedagogical project and encourages teachers to produce the profession between personality and professionality. It describes the internal formative movement to the early childhood school, its importance and the teachers' dissatisfaction with the time allocated to training in this space and with the continuing education offered by the municipal education office, which is insufficient and does not guarantee material and temporal conditions of participation for all. It points out the need for investment in continuing teacher training at the early childhood school, with proposals based on their experiences. It holds up the relevance of publishing academic production in scientific journals for the consolidation of early childhood education as a stage of basic education. The research points out the importance of research that at the same time produces, in parallel, intervention in the CMEI and analysis of scientific texts in the field, promoting dialogues between them without being submissive to each other, revealing the symbiotic commitment with teachers and with the expansion and density of scientificacademic production.